Preparation method and application of light-cured resin
By using a synthetic photocuring resin in the insulation of battery cells of new energy vehicles, the problem of insufficient flame retardant performance of existing UV glue is solved, the excellent insulation and flame retardant performance of the battery cells is achieved, and automated production is supported, which improves production efficiency and safety.
Patent Information
- Application Number
- CN202510003626.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The existing UV glue has problems such as insufficient flame retardant performance, poor insulation performance and inability to achieve automated production in the insulation of new energy vehicle battery cells, which cannot meet the market's demand for high reliability and high bonding strength.
By using a preparation method of a photocuring resin, a photocuring resin with excellent flame retardancy, temperature resistance, flexibility and insulating properties are formed by synthesizing raw materials such as silicone polyols and isocyanates, combined with a capping agent and a polymerization resistor.
It achieves excellent performance of battery cell insulation and protection, has self-flame retardant, can maintain good performance under high temperature and high humidity conditions, and supports automated production, improving production efficiency and safety.
Smart Images

Figure BDA0005226214210000081 
Figure BDA0005226214210000091 
Figure BDA0005226214210000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of UV materials, and in particular relates to a preparation method of a light-curing resin and application thereof. Background Art
[0002] A total of 14.2 million new energy vehicles were delivered in 2023, an increase of more than 35%. Among new energy vehicles, the installed capacity of power batteries is 705.5GWh. The increase in demand for new energy vehicles has also brought certain safety hazards. According to the fire data released by the emergency management department: there were more than 3,000 fires in new energy vehicles throughout 2021, and the spontaneous combustion rate increased by 32% in the first quarter of 2023. On average, 8 new energy vehicles caught fire every day (including spontaneous combustion). The insulation, heat insulation, flame retardancy, and fire prevention of the "three electricity" of new energy vehicles are important links in the safety of the "three electricity".
[0003] At present, the insulation function of the battery cell is achieved by laminating with a "blue film", and its main disadvantages are: it is soft and easy to cause surface damage, which may lead to leakage and fire accidents in the vehicle during use; bubbles are easily generated during the laminating process, affecting the battery life; the bonding part is glue, and local short-term high temperature can also cause abnormal film failure. Patent CN 117229744 A provides a UV glue that has high reliability and high bonding strength such as insulation pressure resistance, water boiling resistance, and salt spray resistance, and can be cured quickly, but the coating scheme in the patent is not flame retardant. Therefore, the existing UV glue has obviously insufficient insulation qualification rate, heat insulation, and flame retardant performance, and cannot realize the laminating method of automated production, which cannot meet the rapidly growing needs of the new energy vehicle market.
[0004] Therefore, it is necessary to develop a photocurable resin having good temperature resistance, excellent flame retardancy and insulation properties, a preparation method thereof and an application thereof. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a photocurable resin, which has excellent flame retardancy, temperature resistance, flexibility and insulation performance, and can better insulate and protect the battery core.
[0006] The present invention also aims to provide application of the photocurable resin.
[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0008] In a first aspect, the present invention provides a method for preparing a photocurable resin, comprising the following steps:
[0009] 1) Synthesis of silicone polyols:
[0010] The hydrogen-terminated polydimethylsiloxane, a compound containing both hydroxyl and (methyl)allyl groups and a first catalyst are mixed and heated to react to obtain a dihydroxy-terminated compound; the dihydroxy-terminated compound, a phosphorus oxychloride compound, a solvent and an acid-binding agent are mixed and heated to react, and the product is washed and dried to obtain an organosilicon polyol.
[0011] 2) Synthesizing a photocurable resin: mixing the organosilicon polyol, isocyanate and second catalyst prepared in step 1) and reacting them to obtain a base resin; mixing the prepared base resin, a capping agent and an optional polymerization inhibitor and reacting them to obtain a photocurable resin.
[0012] Preferably, the hydrogen content of the hydrogen-terminated polydimethylsiloxane is 0.05% to 0.3%, preferably 0.1% to 0.2%; wherein the hydrogen content is the mass content of hydrogen in the hydrogen-terminated polydimethylsiloxane.
[0013] Preferably, the compound containing both hydroxyl and (meth)allyl groups is selected from one or more of eugenol, (meth)allyl glycol, methallyl alcohol, 4-hydroxybutyl (methyl)vinyl ether and homologues thereof, preferably one or more of eugenol and allyl glycol.
[0014] Preferably, the first catalyst is selected from a platinum catalyst, which can be a homogeneous catalyst or a heterogeneous catalyst. Homogeneous catalysts include but are not limited to Speier catalysts and Custer catalysts; heterogeneous catalysts include catalysts formed by adsorbing platinum metal on inorganic particles such as carbon black or alumina; more preferably, it is a Custer catalyst.
[0015] Preferably, the phosphorus oxychloride compound is selected from one or more of phenylphosphoryl dichloride, 4-nitrobenzene phosphorus dichloride, 2-chlorophenyl dichlorophosphine, p-chlorophenyl dichlorophosphate, and m-chlorophenyl dichlorophosphate, more preferably one or more of phenylphosphoryl dichloride, p-chlorophenyl dichlorophosphate, m-chlorophenyl dichlorophosphate, and 4-nitrobenzene phosphorus dichloride.
[0016] Preferably, the molar ratio of active hydrogen in the hydrogen-terminated polydimethylsiloxane to the (meth)allyl group in the compound containing both hydroxyl and (meth)allyl groups is 1:1 to 1:1.1, more preferably 1:1.02 to 1:1.06. The active hydrogen in the hydrogen-terminated polydimethylsiloxane refers to the hydrogen in the Si-H group, which can react with the C=C double bond under platinum catalysis.
[0017] Preferably, the amount of platinum in the first catalyst is 3 to 15 ppm, more preferably 5 to 10 ppm, of the total mass of the hydrogen-terminated polydimethylsiloxane and the compound containing both hydroxyl groups and (meth)allyl groups;
[0018] Preferably, the molar ratio of the phosphorus oxychloride compound to the compound containing both hydroxyl groups and (meth)allyl groups is 0.95:4 to 1.1:4, more preferably 1.02:4 to 1.06:4.
[0019] Preferably, the acid binding agent is pyridine, triethylamine, N,N-diisopropylethylamine (DIEA), sodium carbonate, potassium carbonate, sodium acetate, preferably one or more of triethylamine and potassium carbonate, more preferably one or more of triethylamine, potassium carbonate and sodium carbonate.
[0020] Preferably, the molar ratio of the acid binding agent to the reactive chlorine is 1:0.9 to 1:1, more preferably 1:0.95 to 1:0.98.
[0021] Preferably, the reaction temperature of the hydrogen-terminated polydimethylsiloxane and the compound containing both hydroxyl and (meth)allyl groups is 75 to 85°C.
[0022] Preferably, the reaction temperature of the dihydroxy-terminated compound and the phosphorus oxychloride-containing compound is 20 to 30° C. Preferably, the molar ratio of the organosilicon polyol to the isocyanate is 1.0:1.9 to 1.0:2.15, preferably 1.0:2.0 to 1.0:2.1;
[0023] Preferably, the amount of the second catalyst added is 0.01 to 0.1% of the total mass of the raw material, preferably 0.02 to 0.06%;
[0024] Preferably, the amount of the polymerization inhibitor added is 0 to 0.10% of the total mass of the raw materials, preferably 0.03 to 0.08%;
[0025] Preferably, the end-capping agent is hydroxyacrylate, preferably one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate.
[0026] Preferably, the molar ratio of isocyanate to blocking agent is 1:1 to 1:1.05, preferably 1:1.01 to 1:1.03.
[0027] In the present invention, the second catalyst is an organic tin catalyst, preferably any one or more of dibutyltin dilaurate, dioctyltin dilaurate, stannous octoate, dibutyltin didodecylsulfide, and dibutyltin diacetate, preferably any one or more of dibutyltin dilaurate, stannous octoate, and dioctyltin dilaurate.
[0028] In the present invention, the polymerization inhibitor is a phenolic compound, preferably selected from any one or more of hydroquinone, 4-methoxyphenol, 2,6-di-tert-butyl-p-cresol, 2,5-di-tert-butylhydroquinone, and 2-tert-butylhydroquinone, more preferably any one or more of hydroquinone and 4-methoxyphenol.
[0029] In a second aspect, the present invention provides an application of a photocurable resin prepared by the above method. The photocurable resin can be used in the battery field, especially suitable for battery shell protection, and can be used to prepare UV materials used for battery shell protection.
[0030] A UV material for battery shell protection, comprising the following raw materials in parts by weight:
[0031] Photocurable resin: 30-70 parts;
[0032] Active diluent: 30-70 parts;
[0033] Photoinitiator: 0.5-5 parts;
[0034] Additives: 0.5 to 3 parts.
[0035] The photocurable resin is the photocurable resin described in the present invention.
[0036] The reactive diluent is an acrylate reactive diluent, preferably one or more of tripropylene glycol diacrylate, hexanediol diacrylate, bisphenol A diacrylate, tetraethylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, polyethylene glycol diacrylate, hydroxyethyl (meth) acrylate, cyclotrimethylolpropane formal acrylate, isobornyl (meth) acrylate, tetrahydrofuran acrylate, neopentyl glycol acrylate, tris(2-hydroxyethyl)isocyanuric acid triacrylate, and pentaerythritol triacrylate.
[0037] The photoinitiator is one or more of benzophenone and its derivatives, thioxanthone, anthraquinone, and aryl alkyl ketone compound photoinitiators, preferably one or more of benzoin dimethyl ether, benzophenone, 1-hydroxycyclohexyl benzophenone, 2-methyl-1-(4-methylmercaptophenyl)-2-morpholine-1-propanone, 2-hydroxy-2-methyl-phenylacetone-1, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4-diethylthioxanthone.
[0038] The auxiliary agent is one or more of a leveling agent, a defoaming agent or a wetting and dispersing agent.
[0039] The photocurable resin of the present invention can be used in the field of new energy vehicles, and is particularly suitable for protecting the battery shell of new energy vehicles.
[0040] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0041] The photocurable resin of the present invention has self-flame retardancy, and the UV material for protecting the shell of a new energy battery prepared by using the photocurable resin does not need to add a flame retardant, so that the coating can have good flame retardancy; at the same time, the organic silicon structure in the present invention enables the coating to have excellent aging resistance, so that the coating can still maintain good performance under harsh conditions such as cold and hot shock, high temperature and high humidity; in addition, the organic silicon structure described in the present invention has excellent flexibility, and the coating is not easily damaged when subjected to external force impact, causing battery combustion; compared with traditional blue film, in addition to having good protective performance, the material can also realize automated continuous production, improve production efficiency, and reduce production costs. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] In each embodiment and comparative example of the present invention, the main equipment used is as follows:
[0044] Stirring reactor: RW20 digital, IKA;
[0045] Mixing equipment: DAC600.2 VAC-LR, SpeedMixer;
[0046] UV curing lamp: UV-LED-2, Guangdong Gaoqiong Optoelectronic Equipment Co., Ltd.;
[0047] Universal tensile machine: GT-AI-3000, GOTECH;
[0048] Viscometer: HB, BROOKFIELD;
[0049] Adhesion tester: Airui Instrument Co., Ltd.
[0050] Impact tester: Shenzhen Lai Te Instrument Equipment Co., Ltd.
[0051] In the embodiments and comparative examples of the present invention, the sources of the main raw materials used are as follows. Unless otherwise specified, other raw materials and reagents were purchased from commercial sources:
[0052] Hydrogen-terminated polydimethylsiloxane: RH-H6 (hydrogen content 0.11%), RH-H518 (hydrogen content 0.18%), Ningbo Runhe High-tech Materials Technology Co., Ltd.
[0053] Polyether polyol: PTMEG3000, BASF
[0054] Flame retardant polyol: PF-2014, Zibo Ruinuo New Materials Co., Ltd.
[0055] Isocyanate: IPDI, Wanhua Chemical
[0056] Catalyst: dibutyltin dilaurate, dioctyltin dilaurate, stannous octoate, Aladdin reagent;
[0057] Inhibitors: 4-methoxyphenol, hydroquinone, Aladdin reagent;
[0058] Photoinitiator: TPO, 651, Qiaorun New Materials.
[0059] Active diluent: THEICTA, THFA, Qiaorun New Materials
[0060] Capping agent: Hydroxyethyl acrylate HEA, Hydroxypropyl acrylate HPA, Hydroxyethyl methacrylate HEMA, Hydroxypropyl methacrylate HPMA, Qiaorun New Materials
[0061] Leveling agent: BYK3505, BYK Chemical
[0062] Defoamer: BYK1788, BYK Chemical
[0063] Custer platinum catalyst (platinum content 5000ppm): Beiteli New Materials Co., Ltd.
[0064] Dihydroxy-terminated hydroxy silicone oil: 107 silicone oil (molecular weight 4000), Shenzhen Jipeng Silicone Fluoride Materials Co., Ltd.
[0065] Others: eugenol, allyl glycol, methallyl alcohol, phenylphosphonyl dichloride, 4-nitrobenzene dichlorophosphine, 2-chlorophenyl dichlorophosphine, p-chlorophenyl dichlorophosphate, m-chlorophenyl dichlorophosphate, triethylamine, potassium carbonate, sodium carbonate, acetonitrile, ethyl acetate, Aladdin reagent
[0066] Example 1
[0067] The self-flame retardant photocurable resin PUA-1 is prepared by the following steps:
[0068] 1) Add 910g RH-H6 (hydrogen content 0.11%, molecular weight 1818, 0.5mol) and 167g eugenol (1mol) into a three-necked flask, mix and stir evenly, add 1.2g platinum catalyst (5.57ppm), heat to 75°C, react for 3 hours, and obtain a dihydroxy-terminated compound. Add 48.8g (0.25mol) phenylphosphonic acid dichloride and mix and stir evenly, add triethylamine (55.3g) / acetonitrile (1200ml) mixed solvent, and react at 25°C for 5h; after the reaction, wash the product with ethyl acetate, and then vacuum dry at 60°C for 8h to obtain self-flame retardant silicone polyol FA1 (molecular weight 4400);
[0069] 2) Add 220g of organosilicon polyol FA1 (0.05mol) and 22.7g of IPDI (0.102mol) to a three-necked flask, mix and stir evenly, add 0.12g of dibutyltin dilaurate (0.05%), heat to 70°C, and react for 2 hours. After the reaction is completed, add 0.12g of 4-methoxyphenol (0.05%) and 12g of HEA (0.103mol), start stirring, heat to 75°C, and react for 2 hours to obtain self-flame retardant photocurable resin PUA-1.
[0070] Example 2
[0071] The self-flame retardant polyurethane acrylate resin PUA-2 is prepared by the following steps:
[0072] 1) Add 556gRH-H518 (hydrogen content 0.18%, molecular weight 1111, 0.5mol) and 106g allyl glycol (1.04mol) into a three-necked flask, mix and stir evenly, add 1.2g platinum catalyst (9ppm), heat to 85°C, react for 3 hours, and obtain a dihydroxy-terminated compound. Add 69.2g (0.27mol) 4-nitrobenzene phosphorus dichloride and mix and stir evenly, add a mixed solvent of 77.3g potassium carbonate / acetonitrile (1200ml), and react at 20°C for 5h; after the reaction, wash the product with ethyl acetate, and then vacuum dry it at 60°C for 8h to obtain a self-flame retardant silicone polyol FA2 (molecular weight 2800);
[0073] 2) Add 140g of organosilicon polyol FA2 (0.05mol) and 22.92g of IPDI (0.103mol) to a three-necked flask, mix and stir evenly, add 0.1g of stannous octoate (0.06%), heat to 75°C, and react for 2 hours. After the reaction is completed, add 0.1g of 4-methoxyphenol (0.06%) and 13.8g of HPA (0.106mol), start stirring, heat to 75°C, and react for 2 hours to obtain self-flame retardant photocurable resin PUA-2.
[0074] Example 3
[0075] The self-flame retardant polyurethane acrylate resin PUA-3 is prepared by the following steps:
[0076] 1) Add 556gRH-H518 (hydrogen content 0.18%, molecular weight 1111, 0.5mol) and 72gmethallyl alcohol (1.06mol) into a three-necked flask, mix and stir evenly, add 0.9g (7ppm) of platinum catalyst, heat to 75°C, react for 3 hours, and obtain a dihydroxy-terminated compound. Add 68.6g (0.28mol) of 2-chlorophenyl dichlorophosphine, mix and stir evenly, add a mixed solvent of 60.6g sodium carbonate / acetonitrile (1200ml), and react at 25°C for 5h; after the reaction, wash the product with ethyl acetate, and then vacuum dry it at 60°C for 8h to obtain a self-flame retardant silicone polyol FA3 (molecular weight 2800);
[0077] 2) Add 140g of organosilicon polyol FA3 (0.05mol) and 23.14g of IPDI (0.104mol) to a three-necked flask, mix and stir evenly, add 0.05g of dioctyltin dilaurate (0.03%), heat to 75°C, and react for 2 hours. After the reaction is completed, add 0.05g of 4-methoxyphenol (0.03%) and 15.4g of HPMA (0.107mol), start stirring, heat to 75°C, and react for 2 hours to obtain self-flame retardant photocurable resin PUA-3.
[0078] Example 4
[0079] The self-flame retardant polyurethane acrylate resin PUA-4 is prepared by the following steps:
[0080] 1) Add 556gRH-H518 (hydrogen content 0.18%, molecular weight 1111, 0.5mol) and 76gmethallyl alcohol (1.06mol) into a three-necked flask, mix and stir evenly, add 0.9g platinum catalyst (7ppm), heat to 85°C, react for 3 hours, and obtain a dihydroxy-terminated compound. Add 34.3g of p-chlorophenyl dichlorophosphate and p-chlorophenyl dichlorophosphate, mix and stir evenly, add a mixed solvent of 57.57g triethylamine / acetonitrile (1200ml), and react at 25°C for 5h; after the reaction, wash the product with ethyl acetate, and then vacuum dry it at 60°C for 8h to obtain a self-flame retardant silicone polyol FA4 (molecular weight 2800);
[0081] 2) Add 140g of organosilicon polyol FA4 (0.05mol) and 23.14g of IPDI (0.104mol) to a three-necked flask, mix and stir evenly, add 0.05g of dioctyltin dilaurate (0.03%), heat to 75°C, and react for 2 hours. After the reaction is completed, add 0.05g of hydroquinone (0.03%) and 13.9g of HEMA (0.107mol), start stirring, heat to 80°C, and react for 2 hours to obtain self-flame retardant photocurable resin PUA-4.
[0082] Embodiments 5 to 8
[0083] According to the raw material ratios in Table 1 below, the self-flame retardant photocurable resins prepared in Examples 1 to 4 were mixed and stirred evenly with auxiliary agents, photoinitiators, and reactive diluents in a sealed container at a temperature not exceeding 40° C. to obtain a self-flame retardant UV material.
[0084] Comparative Example 1
[0085] The steps for preparing the photocurable resin PUA-5 are as follows:
[0086] 1) Add 2000g 107 silicone oil (0.5mol) and 227g IPDI (1.02mol) to a three-necked flask, mix and stir evenly, add 1.1g dibutyltin dilaurate (0.05%), heat to 70°C, and react for 2 hours. After the reaction is completed, add 1.1g 4-methoxyphenol (0.05%) and 116g HEA (1.03mol), start stirring, heat to 75°C, and react for 2 hours to obtain a photocurable resin PUA-5.
[0087] Comparative Example 2
[0088] Preparation of polyurethane acrylate resin PUA-6, the steps are:
[0089] 1) Add 1500g PTMEG3000 (0.5mol) and 231g IPDI (1.04mol) to a three-necked flask, mix and stir evenly, add 0.52g dibutyltin dilaurate (0.03%), heat to 75°C, and react for 2 hours. After the reaction, add 0.52g 4-methoxyphenol (0.03%) and 139g HEMA (1.07mol), start stirring, heat to 80°C, and react for 2 hours to obtain a photocurable resin PUA-6.
[0090] Comparative Example 3
[0091] Preparation of polyurethane acrylate resin PUA-7, the steps are:
[0092] 1) Add 300g PF-2014 (0.5mol) and 231g IPDI (1.04mol) to a three-necked flask, mix and stir evenly, add 0.52g dioctyltin dilaurate (0.03%), heat to 75°C, and react for 2 hours. After the reaction, add 0.52g 4-methoxyphenol (0.03%) and 139g HEMA (1.07mol), start stirring, heat to 80°C, and react for 2 hours to obtain the photocurable resin PUA-7.
[0093] Comparative Examples 4 to 7
[0094] According to the raw material ratios in Table 1 below, the photocurable resins prepared in Comparative Examples 1 to 3 were mixed and stirred evenly with the auxiliary agent, the photoinitiator, and the reactive diluent in a sealed container at a temperature not exceeding 40° C. to obtain a UV material without self-flame retardancy.
[0095] In each embodiment and comparative example of the present invention, the main test characterization methods used are as follows, and the results are shown in Table 1:
[0096] Adhesion: 100-grid method, test standard GB / T 9286-2021;
[0097] Flame retardancy: UL94
[0098] Bonding strength: GB / T33334-016, base material PC, aluminum 6061;
[0099] Impact strength: GB / T 1732-2020
[0100] Hardness / Shore A: GB / T 39693.7-2022.
[0101] Table 1: Formulas and test results of Examples 5 to 8 and Comparative Examples 4 to 7 (the amount of each raw material added is in parts by mass):
[0102]
[0103]
[0104]
[0105] Compared with Comparative Example 4, Example 5, Example 6, Example 7, and Comparative Example 6, and Example 8, the Examples and Comparative Examples have good bonding properties, adhesion, and impact properties, indicating that the Examples and Comparative Examples have good mechanical properties; in addition, the flame retardant properties of the Examples are better than those of the Comparative Examples, indicating that the Examples have better self-flame retardancy, indicating that the synthesized flame retardant polyol is beneficial to improving the flame retardant properties of UV materials;
[0106] The bonding strength changes of the embodiments after hot and cold shock aging are smaller than those of the comparative examples, the adhesion of the embodiments does not change, comparative examples 4 and 7 contain a large amount of silicone components, and the adhesion is level 0, which does not change; comparative examples 5 and 6 have no or a small amount of silicone components, and the adhesion becomes level 1, indicating that the silicone component is beneficial to improving the hot and cold shock resistance of the coating; the impact strength of the embodiments does not change after hot and cold shock aging, and the impact strength of the comparative examples is reduced, indicating that the embodiments have good hot and cold shock resistance.
[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a photocurable resin, characterized in that: The following steps are involved: 1) Synthesis of silicone polyols: The hydrogen-terminated polydimethylsiloxane, the compound containing both hydroxyl and (methyl)allyl groups and the first catalyst are mixed, and heated to react to obtain a dihydroxy-terminated compound; the dihydroxy-terminated compound, a phosphorus oxychloride compound, a solvent and an acid-binding agent are mixed, and heated to react, and the product is washed and dried to obtain an organosilicon polyol; 2) Synthesizing a photocurable resin: mixing the organosilicon polyol, isocyanate and second catalyst prepared in step 1) and reacting them to obtain a base resin; mixing the prepared base resin, a capping agent and an optional polymerization inhibitor and reacting them to obtain a photocurable resin.
2. The preparation method according to claim 1, characterized in that: The hydrogen content of the hydrogen-terminated polydimethylsiloxane is 0.05% to 0.3%, preferably 0.1% to 0.2%; wherein the hydrogen content is the mass content of hydrogen in the hydrogen-terminated polydimethylsiloxane; Preferably, the compound containing both hydroxyl and (meth)allyl groups is selected from one or more of eugenol, (meth)allyl glycol, methallyl alcohol, 4-hydroxybutyl (methyl) vinyl ether and homologues thereof, preferably one or more of eugenol and allyl glycol; Preferably, the first catalyst is selected from a platinum catalyst, which may be a homogeneous catalyst or a heterogeneous catalyst. The homogeneous catalyst includes but is not limited to a Speier catalyst and a Custer catalyst; the heterogeneous catalyst includes a catalyst formed by adsorbing platinum metal on inorganic particles such as carbon black or alumina; and the Custer catalyst is more preferably; Preferably, the phosphorus oxychloride compound is selected from one or more of phenylphosphoryl dichloride, 4-nitrobenzene phosphorus dichloride, 2-chlorophenyl dichlorophosphine, p-chlorophenyl dichlorophosphate, and m-chlorophenyl dichlorophosphate, more preferably one or more of phenylphosphoryl dichloride, p-chlorophenyl dichlorophosphate, m-chlorophenyl dichlorophosphate, and 4-nitrobenzene phosphorus dichloride.
3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of active hydrogen in the hydrogen-terminated polydimethylsiloxane to the (meth)allyl group in the compound containing both hydroxyl and (meth)allyl groups is 1:1 to 1:1.1, more preferably 1:1.02 to 1:1.06; Preferably, the amount of platinum in the first catalyst is 3 to 15 ppm, more preferably 5 to 10 ppm, of the total mass of the hydrogen-terminated polydimethylsiloxane and the compound containing both hydroxyl groups and (meth)allyl groups; Preferably, the molar ratio of the phosphorus oxychloride compound to the compound containing both hydroxyl groups and (meth)allyl groups is 0.95:4 to 1.1:4, more preferably 1.02:4 to 1.06:
4.
4. The preparation method according to any one of claims 1 to 3, characterized in that The acid binding agent is pyridine, triethylamine, N,N-diisopropylethylamine, sodium carbonate, potassium carbonate, sodium acetate, preferably one or more of triethylamine and potassium carbonate, more preferably one or more of triethylamine, potassium carbonate, sodium carbonate; Preferably, the molar ratio of the acid binding agent to the reactive chlorine is 1:0.9 to 1:1, more preferably 1:0.95 to 1:0.
98.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The reaction temperature of hydrogen-terminated polydimethylsiloxane and compounds containing both hydroxyl and (meth)allyl groups is 75 to 85°C; And / or, the reaction temperature of the dihydroxy-terminated compound and the phosphorus oxychloride-containing compound is 20-30°C.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The molar ratio of the organosilicon polyol to the isocyanate is 1.0:1.9 to 1.0:2.15, preferably 1.0:2.0 to 1.0:2.1; Preferably, the amount of the second catalyst added is 0.01 to 0.1% of the total mass of the raw material, preferably 0.02 to 0.06%; Preferably, the amount of the polymerization inhibitor added is 0 to 0.10% of the total mass of the raw materials, preferably 0.03 to 0.08%; Preferably, the end-capping agent is a hydroxyacrylate, preferably one or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate; Preferably, the molar ratio of isocyanate to blocking agent is 1:1 to 1:1.05, preferably 1:1.01 to 1:1.
03.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The second catalyst is an organic tin catalyst, preferably any one or more of dibutyltin dilaurate, dioctyltin dilaurate, stannous octoate, dibutyltin didodecylsulfide, and dibutyltin diacetate, preferably any one or more of dibutyltin dilaurate, stannous octoate, and dioctyltin dilaurate; Preferably, the polymerization inhibitor is a phenolic compound, preferably selected from any one or more of hydroquinone, 4-methoxyphenol, 2,6-di-tert-butyl-p-cresol, 2,5-di-tert-butylhydroquinone, and 2-tert-butylhydroquinone, more preferably any one or more of hydroquinone and 4-methoxyphenol.
8. An application of a photocurable resin prepared by the preparation method according to any one of claims 1 to 7, wherein the photocurable resin can be used in the battery field, especially suitable for battery shell protection, and can be used to prepare UV materials used for battery shell protection.
9. A UV material for battery shell protection, comprising the following raw materials in parts by weight: Photocurable resin: 30-70 parts; Active diluent: 30-70 parts; Photoinitiator: 0.5-5 parts; Additives: 0.5-3 parts; The photocurable resin is a photocurable resin prepared by the preparation method according to any one of claims 1 to 7; Preferably, the reactive diluent is an acrylate reactive diluent, preferably one or more of tripropylene glycol diacrylate, hexanediol diacrylate, bisphenol A diacrylate, tetraethylene glycol diacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, polyethylene glycol diacrylate, hydroxyethyl (meth) acrylate, cyclotrimethylolpropane formal acrylate, isobornyl (meth) acrylate, tetrahydrofuran acrylate, neopentyl glycol acrylate, tris (2-hydroxyethyl) isocyanuric acid triacrylate, and pentaerythritol triacrylate; Preferably, the photoinitiator is one or more of benzophenone and its derivatives, thioxanthone, anthraquinone, and aryl alkyl ketone compound photoinitiators, preferably one or more of benzoin dimethyl ether, benzophenone, 1-hydroxycyclohexyl benzophenone, 2-methyl-1-(4-methylmercaptophenyl)-2-morpholine-1-propanone, 2-hydroxy-2-methyl-phenylacetone-1, 2,4,6,-trimethylbenzoyl-diphenylphosphine oxide, bis(2,4,6,-trimethylbenzoyl)phenylphosphine oxide, and 2,4-diethylthioxanthone; Preferably, the auxiliary agent is one or more of a leveling agent, a defoaming agent or a wetting and dispersing agent.
10. Use of the photocurable resin according to claim 8 or 9, wherein the photocurable resin can be used in the field of new energy vehicles, and is particularly suitable for protecting the battery shell of new energy vehicles.
Citation Information
Patent Citations
High-reliability fast-curing UV adhesive for outer layer protection of power battery as well as preparation method and application of high-reliability fast-curing UV adhesive
CN117229744A
Ultraviolet curing adhesive and preparation method thereof
CN115678487A
Waterborne polyurethane fireproof coating and preparation process thereof
CN117363193A
polysiloxane polyol
JP2001512163A
Polyorganosiloxane, a method for preparing thereof and copolycarbonate resin
KR1020150003682A
Cited By
Nano-modified heat-conducting three-proofing insulating resin composition and preparation method thereof
CN121182348A